Biopolitics: Slavery, Racism and Eugenics in Latin America (Journal of Advanced Research in Social Sciences, 2020)
This article analyzes historical population changes as mechanisms of biopower in Latin America: during colonization, the crisis of indigenous groups, the arrival of enslaved Africans and, later, the immigration of free settler Europeans to replace both indigenous people and Africans as workforce and land property. The perspectives of settler colonialism and biopower are adopted to understand how sequential mechanisms of biopolitics were implemented in settler societies, through genocide and the assimilation of the majority, who were progressively being eliminated or transformed into minorities. The method includes literature review of the predominant concepts, discourses and practices established in the biopolitical process attached to settler colonialism, as well as the methods, institutions, policies and actors who built these modes of biopower. The results show the adoption of several biopolitics mechanisms, such as wars, epidemics, over-exploitation, land confiscation, the kidnaping of women, inferiorization, human trafficking and cruel punishments, during colonialism, as well as miscegenation, isolation and the marginalization and disappearing of those resisting in the transition to settler colonialism, when eugenic policies of fertility control and European immigration were implemented in order to whiten the population, which reinforced, articulated and validated the persistent racism, discrimination against and disadvantages forced upon these populations.